Empirical analysis of the factors determining the profitability of insurance companies in the Republic of North Macedonia - Gockov, GJorgji; Kamenjarska Tanja (Romanian Academy, 2021)
The aim of this paper is to identify and assess industry-specific and macroeconomic variables that determine the profitability of insurance companies in the Republic of North Macedonia through panel data for fourteen, life and non-life insurance companies. In the model specification, ROA was chosen as a measure of profitability and is set to be a dependent variable while GDP, inflation rate, underwriting risk, growth, financial investment growth rate, combined ratio, market share and leverage are set to be explanatory variables. Results from the use of dynamic panel analysis show that growth, leverage, combined ratio, underwriting risk, lagged return on assets and inflation rate have a negative and statistically significant impact on firm performance. On the other side, market share and financial investments have statistically positive relationship with the profitability. Based on the results, policy recommendations are provided for improving the profitability of insurance companies.
Keywords: insurance companies, financial performance, GMM model, Republic of North Macedonia, profitability